ANALISIS KEGAGALAN PADA PATAHAN MATA BOR TIPE HIGH SPEED STEEL - Ariyanto, Sudirman Rizki; Pratama, Muhammad Yandi; Warju, Warju; Hidayatullah, Rachmad Syarifudin; Anwari, Muhammad Syahrul (Steam Engineering, 2025)
Drill bit failure in the drilling process often occurs due to exposure to mechanical, thermal, and chemical loads during operation. Nachi HSS drill bits, as critical components in the manufacturing industry, are prone to sudden wear and breakage due to dynamic processes involving material fragmentation, friction, and increased local temperatures. This study analyses the root cause of Nachi HSS drill bit failure through fracture investigation, chemical composition, and microstructure. The analysis methods include macroscopic testing to identify fracture patterns, optical microscopy to evaluate surface deformation, and X-ray Fluorescence (XRF) testing to verify material composition. The results showed that the fault was a brittle fracture due to a mismatch in chemical composition: molybdenum (Mo) levels were not detected. At the same time, chromium (Cr) and vanadium (V) only reached 3.85% and 0.95%, 0.45% lower than factory standards. This deficiency reduces resistance to thermomechanical loads, triggering stress concentration and rapid crack propagation during the drilling of ST37 steel material at a speed of 1,800 RPM. These findings emphasize the importance of quality control of material composition and optimization of operating parameters to prevent premature failure.